Vehicle-mounted net sampling of airborne micro-Heteroptera in western Liberia, West Africa: 1. Isometopinae (Miridae) - Krüger, Andreas (Zootaxa, 2018)
A vehicle-mounted “car-net” is a rarely used technique of insect sampling. In Liberia, it was used over several consecutive months, and the first results of taxonomic analyses of Heteroptera from the by-catch are presented, namely on the mirid subfamily Isometopinae (“jumping tree bugs”). So far, no isometopine species have been known from Liberia. New records of Isometopinae in Liberia are provided including: Isometopus slateri (Akingbohungbe), Myiomma cobbeni Akingbohungbe, M. rubra Smith, and M. rubrovenata Smith. Additional new species are described, including: Isometopus bongensis sp. nov., Paloniella garmsi sp. nov., P. erinacea sp. nov., Ptisca liberiense sp. nov., Myiomma albostiolata sp. nov., M .brunnea sp. nov., M. fuscipes sp. nov., M. goellneri sp. nov. and M. variabilis sp. nov. A new genus with one included species is similarly described as follows: Bongiella nodistylis gen. nov. et sp. nov.